Identification of the major photodegradant in metronidazole by LC-PDA-MS and its reveal in compendial methods - Chen, Mei-Ling; Xu, Hong-Xia; Yuan, Wei-Feng; Zhao, Sui-Hong; Li, Xue; Zhu, Lan-Xin; Shen, Zong-Yong; Liu, Yu-Jing; Wang, Ming-Juan; Ma, Ang; Hoogmartens, Jos; Adams, Erwin (Scientific reports, 2022)
Metronidazole in aqueous solution is sensitive to light and UV irradiation, leading to the formation of N -(2-hydroxyethyl)-5-methyl-l,2,4-oxadiazole-3-carboxamide. This is revealed here by liquid chromatography with tandem photo diode array detection and mass spectrometry (LC-PDA-MS) and further verified by comparison with the corresponding reference substance and proton nuclear magnetic resonance ( 1 H-NMR). However, in current compendial tests for related substances/organic impurities of metronidazole, the above photolytic degradant could not be detected. Thus, when photodegradation of metronidazole occurs, it could not be demonstrated. In our study, an improved LC method was developed and validated, which includes a detection at a wavelength of 230 nm and optimization of mobile phase composition thereby a better separation was obtained.